PENGARUH KEAKTIFAN BERORGANISASI DAN PRESTASI AKADEMIK TERHADAP KESIAPAN KERJA DENGAN SOFT SKILL SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Mahasiswa Universitas Bina Insan) - Heni Angiasari; Ronal Aprianto; Fitria; Wisdalia Maya Sari (Program Studi Magister Ilmu Manajemen Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2025)
This study aims to examine the influence of organizational involvement and academic achievement on students’ job readiness, with soft skills serving as an intervening variable, focusing on students at Universitas Bina Insan. The research employed a quantitative descriptive approach, involving 85 respondents selected from a population of 543 students using a combination of stratified random sampling and purposive sampling techniques. The analysis revealed that active participation in student organizations does not have a significant effect on job readiness, either directly or indirectly through soft skills. In contrast, academic achievement was found to significantly influence job readiness, both directly and indirectly through enhanced soft skills. Furthermore, when analyzed simultaneously, both organizational involvement and academic achievement demonstrated a significant combined effect on students’ job readiness. These findings highlight the critical role of academic performance and soft skill development as key factors in preparing students to meet the demands of an increasingly competitive labor market.